REAKSI PASAR MODAL TERHADAP PEMILIHAN UMUM PRESIDEN PADA JASA PERBANKAN DI INDONESIA - Widya Presilia; Dwi Kartikasari (ABEC Indonesia, 2021)
As one of the largest democracies in the world, Indonesia held its twelfth election which took place openly, freely, publicly, honestly and fairly on April 17, 2019. A number of studies suggest that elections risk causing fluctuations that investors generally avoid. The purpose of this study is to determine whether the risk of fluctuation was proven so that there were significant differences in the average stock price, stock return, and trading volume activity before and after the presidential election event. This paper is an event research. The population of this study was all banking companies listed on the Indonesia Stock Exchange that is 45 banking companies for the duration of five days before and after the 2019 presidential election on two types of data, namely price and number of traded shares with a total of 900 observations. Comparative test analysis is implemented in the form of paired sample t-test when the data is normally distributed and/or non-parametric test (Wilcoxon test) when the data is not normally distributed. The results of this study are that there was no significant difference between the average stock price, stock return and trading volume activity before and after the 2019 presidential election so the risk of fluctuation due to elections was not empirically proven in Indonesia.